Functional diversification of duplicated CYC2 clade genes in regulation of inflorescence development in Gerbera hybrida (Asteraceae). (15th July 2014) - Juntheikki‐Palovaara, Inka; Tähtiharju, Sari; Lan, Tianying; Broholm, Suvi K.; Rijpkema, Anneke S.; Ruonala, Raili; Kale, Liga; Albert, Victor A.; Teeri, Teemu H.; Elomaa, Paula
Summary The complex inflorescences (capitula) of Asteraceae consist of different types of flowers. In Gerbera hybrida (gerbera), the peripheral ray flowers are bilaterally symmetrical and lack functional stamens while the central disc flowers are more radially symmetrical and hermaphroditic. Proteins of the CYC2 subclade of the CYC/TB1‐like TCP domain transcription factors have been recruited several times independently for parallel evolution of bilaterally symmetrical flowers in various angiosperm plant lineages, and have also been shown to regulate flower‐type identity in Asteraceae. The CYC2 subclade genes in gerbera show largely overlapping gene expression patterns. At the level of single flowers, their expression domain in petals shows a spatial shift from the dorsal pattern known so far in species with bilaterally symmetrical flowers, suggesting that this change in expression may have evolved after the origin of Asteraceae. Functional analysis indicates that GhCYC2, GhCYC3 and GhCYC4 mediate positional information at the proximal–distal axis of the inflorescence, leading to differentiation of ray flowers, but that they also regulate ray flower petal growth by affecting cell proliferation until the final size and shape of the petals is reached. Moreover, our data show functional diversification for the GhCYC5 gene. Ectopic activation of GhCYC5 increases flower density in the inflorescence, suggesting that GhCYC5 may promote the flower initiation rate during expansion of the capitulum. Our data thus indicate that modification of the ancestral network of TCP factors has, through gene duplications, led to the establishment of new expression domains and to functional diversification.